1990
DOI: 10.1039/c39900000871
|View full text |Cite
|
Sign up to set email alerts
|

A silver co-ordination polymer bridged by a conjugated ligand

Abstract: The crystallographic characterization of the first well defined co-ordination polymer in which silver ions are linked by a bridging conjugated organic ligand is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The Ag2-O1 bond distance of 2.382(4) Å compares well with literature values for tetracoordinate silver complexes; [29][30][31] the long Ag1-O2 distance of 2.601(4) Å is consistent with a weak bond, as has been found in other silver-triflate species.…”
Section: Resultssupporting
confidence: 86%
“…The Ag2-O1 bond distance of 2.382(4) Å compares well with literature values for tetracoordinate silver complexes; [29][30][31] the long Ag1-O2 distance of 2.601(4) Å is consistent with a weak bond, as has been found in other silver-triflate species.…”
Section: Resultssupporting
confidence: 86%
“…(i) [Au(acac)(PPh 3 )], (ii) [O(AuPPh 3 ) 3 ]ClO 4 , (iii) Ag(OTf), (iv) [Ag(OTf)(PPh 3 )].of the Cp-rings C(1-5) and C(6-10), respectively)]. The dihedral angle between the benzimidazole plane and Cprings are equal to 58.4°.The Ag-O distances (2.5092(16) and 2.6271(15) Å ) lie among the longest observed in literature for four-coordinated silver complexes[25][26][27]. The longer, 2.6271(15) Å Ag-O2#, indicates a weaker bond to the second triflate unit.…”
mentioning
confidence: 84%
“…3 Polymeric silver() complexes with inorganic 4-7 and organic 8-12 ligands have been reported, but the synthesis and characterisation of many of these compounds is incomplete because of their insolubilities. 10, 11 Richmond and co-workers have shown that AgO 3 SCF 3 with 1,4-di-tert-butyl-1,4-diazabuta-1,3-diene gives a polymeric derivative, 11 but a reversible polymerisation reaction results when the related phenyl derivatives XC 6 H 4 CHNC 2 H 4 NCHC 6 H 4 X (X = Cl or Br) are added in a 1 : 2 molar ratio. 12 The study of silver() with simple acyclic nitrogen-donor ligands has, however, been relatively neglected.…”
mentioning
confidence: 99%